2000
DOI: 10.1097/00002371-200003000-00004
|View full text |Cite
|
Sign up to set email alerts
|

An Acidic Microenvironment Inhibits Antitumoral Non–Major Histocompatibility Complex-Restricted Cytotoxicity: Implications for Cancer Immunotherapy

Abstract: Local immunosuppression may explain the failure of an effective immune response against solid tumors. Although it is well known that the interstitial pH is significantly lower in solid tumors than in normal tissue, only a few studies in the mouse system have investigated the influence of this acidic milieu on the anti-tumoral cytotoxic response. Here the authors report the suppression of human non-major histocompatibility complex (MHC)-restricted cytotoxicity against tumor cells by an acidic extracellular pH (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…In comparison with normal tissues, solid tumors often possess regions with an acidic microenvironment. In a recent report we were able to demonstrate that an acidic extracellular pH inhibits the cell-mediated cytotoxicity of human NK and LAK cells (7). Thus, interstitial pH seems to be one important factor contributing to the impairment of immune functions in cancer.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In comparison with normal tissues, solid tumors often possess regions with an acidic microenvironment. In a recent report we were able to demonstrate that an acidic extracellular pH inhibits the cell-mediated cytotoxicity of human NK and LAK cells (7). Thus, interstitial pH seems to be one important factor contributing to the impairment of immune functions in cancer.…”
Section: Discussionmentioning
confidence: 85%
“…Recognition and concomitant binding of effector cells to target cells by adhesion molecules is an initial event in the multistep killing process (8,9). Yet, the expression of different adhesion molecules was not affected by acidic pH e (7). In the present study we focused on subsequent steps involved in the killing process and their potential inhibition by low pH e .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The data presented here suggest that the ability of TIL to secrete cytokines [17,35] and to overexpress activation markers [36,37] in response to polyclonal stimuli differs in cultures at physiological pH e or at the low pH e commonly found in tumor microenvironment. Studies on proliferation and cytotoxic activity in an acidic medium have shown that both NK and LAK cells display impaired cytotoxic activity against tumor cells [38,39], and low levels of cytokine production and metabolic activity [40] in such conditions. Other studies have also shown that hypoxia and low pH e inhibit both NK activity and IL-2-induced proliferation [41][42][43].…”
Section: Discussionmentioning
confidence: 99%